The role of corrosion inhibition in the mitigation of CaCO3 scaling on steel surface. (1st August 2018) - Zhu, Tianzhen; Wang, Lida; Sun, Wen; Wang, Meng; Tian, Jisheng; Yang, Zhengqing; Wang, Suilin; Xia, Liang; He, Shaohui; Zhou, Yingzheng; Liu, Guichang
Highlights: Corrosion induced micro-cathodic effect on interfacial CaCO3 scaling was studied. Steel/water interfacial corrosion behaviour was tuned by introducing NaNO2 . Scaling at corrosion-inhibiting interfaces was shown at different temperatures. pH rise at micro cathodes dominates interfacial scaling via promoting nucleation. Heating cannot cause evident scaling once micro-cathodic process is suppressed. Abstract: Corrosion-induced CaCO3 scaling is extremely widespread at metal/water interface. However, the anti-scale and anti-corrosion behaviour of existing inhibitors have mostly been investigated separately without considering their interaction. Herein, the roles of corrosion inhibition in mitigating interfacial scaling were evaluated on carbon steel and stainless steel by introducing NaNO2 to enhance their corrosion resistance. Results reveal that corrosion-induced pH increase at micro cathodes dominates the interfacial scaling processes by inducing rapid nucleation. A temperature elevation promotes interfacial scaling mainly through aggravating steel corrosion. Once the micro cathodic processes are inhibited, CaCO3 scaling can be evidently retarded even at elevated temperatures.